Anti-radiation metal layered composite material and preparation method thereof
By using composite rolling and heat treatment technology of Al-3.5Cu-2Mg-Ni alloy and tantalum tungsten alloy, metal layered composite materials with high mechanical properties and excellent radiation resistance were prepared, which solved the problems of low mechanical properties and radiation shielding efficiency of existing materials, and met the needs of aerospace vehicles and deep space exploration tasks.
Patent Information
- Application Number
- CN202411867810.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing aluminum/tantalum layered composite panels have low room temperature mechanical properties, which cannot meet the needs of load-bearing structural parts of aerospace vehicles, and at the same time, the space radiation shielding efficiency is also low, which cannot meet the needs of deep space exploration tasks.
The radiation-resistant metal layered composite material was prepared by composite rolling method using Al-3.5Cu-2Mg-Ni alloy and tantalum tungsten alloy, and was subjected to homogenization treatment, hot rolling, annealing, solid solution treatment and aging treatment to improve the mechanical properties and radiation shielding properties of the material.
It significantly improves tensile strength, yield strength and shear strength, has excellent radiation resistance, and has more than 790% shielding and protection effect than single aluminum materials, meeting the needs of deep space exploration tasks.
Smart Images

Figure CN119657633A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of aluminum alloy composite materials, and in particular to a radiation-resistant metal layered composite material and a preparation method thereof. Background Art
[0002] Aerospace vehicles mainly include deep space exploration, medium and high orbits, commercial space satellites and other orbital aircraft. When operating in orbit, they are bombarded by space radiation particles, causing serious total dose effects, which seriously threaten the life and reliability of aerospace products in orbit. At present, my country's aerospace department mainly uses single-element aluminum alloy as a protective material for space radiation protection. However, as my country's deep space exploration and navigation satellites are included in major national strategic tasks, single-element aluminum alloy can no longer fully meet the total dose radiation resistance requirements. Foreign countries have developed dissimilar metal patch-type protective materials of aluminum and tantalum, but the need for additional supporting and connecting structures increases the mass and increases the launch cost.
[0003] An existing aluminum-tantalum composite plate and its preparation method use vacuum diffusion welding to prepare the aluminum-tantalum composite plate, but the preparation process has high requirements on the surface of the plate, and it needs to be polished to a mirror surface with 600#, 800#, 1000#, and 1200# sandpaper in sequence, which is not suitable for industrial production, and the maximum tensile strength is 39MPa, which cannot meet the mechanical performance requirements of aerospace products. There is also a method for preparing aluminum / aluminum / tantalum three-layer composite materials by different temperature rolling. The shear strength of the aluminum-tantalum layered composite plate prepared by the method of heating aluminum and not heating tantalum reaches 70MPa; and a lightweight and high-strength aluminum-tantalum composite metal plate and its rolling forming method, which needs to evacuate the heating furnace and pass argon gas for protection during the rolling process, and the production cost is relatively high.
[0004] In summary, the room temperature mechanical properties of aluminum / tantalum layered composite plates prepared by existing technologies are relatively low, and they cannot be used as load-bearing structural parts for aerospace vehicle payloads. In addition, the space radiation shielding efficiency is low, and it cannot meet the needs of deep space exploration missions. In addition, during the heat treatment process to improve the mechanical and interface shear properties of aluminum / tantalum composite materials, aluminum / tantalum composite materials may experience problems such as surface oxidation and the formation of interface compounds. At the same time, due to the large difference in the thermal expansion coefficients of the two, the interface layer of the composite interface is delaminated under the cold and hot cycle service environment, resulting in product failure. Summary of the invention
[0005] In order to solve the above-mentioned deficiencies in the art, the present application aims to provide a radiation-resistant metal layered composite material and a preparation method thereof.
[0006] According to one aspect of the present application, a method for preparing a radiation-resistant metal layered composite material is provided, comprising:
[0007] Melting and casting Al-3.5Cu-2Mg-Ni alloy ingot;
[0008] The Al-3.5Cu-2Mg-Ni alloy ingot is homogenized, hot rolled, and annealed;
[0009] Composite rolling of the annealed Al-3.5Cu-2Mg-Ni alloy ingot and a tantalum-tungsten alloy plate to obtain a radiation-resistant metal layered composite material;
[0010] Among them, the composition and weight percentage of the Al-3.5Cu-2Mg-Ni alloy ingot are: Si: ≤0.5%, Fe: 0.2~0.6%, Cu: 3~3.8%, Mn: ≤0.05%, Mg: 1.8~2.4%, Ni: 0.8~1.2%, Zn: ≤0.3%, Ti: ≤0.5%, the individual content of other elements is ≤0.05%, the total amount is ≤0.15%, and the balance is aluminum.
[0011] According to some embodiments of the present application, the homogenization treatment includes: heating to 492-498°C at a rate of 80-100°C / h, keeping the temperature for ≥1.5h per 40mm according to the thickness of the alloy ingot, rapidly heating to 500-510°C after the insulation is completed, keeping the temperature for 10-15h, and air cooling after the insulation time is completed.
[0012] According to some embodiments of the present application, the hot rolling temperature is 470±10°C, the heating time is ≥1.5h, the start rolling temperature is 440±20°C, the final rolling temperature is ≥270°C, and the reduction in each pass is ≤40%.
[0013] According to some embodiments of the present application, the annealing temperature is 350-380° C. and the holding time is 3-6 hours.
[0014] According to some embodiments of the present application, the reduction in a single pass of composite rolling is 35-40%.
[0015] According to some embodiments of the present application, the preparation method further includes: subjecting the radiation-resistant metal layered composite material to solution treatment and aging treatment in sequence.
[0016] According to some embodiments of the present application, the solution treatment includes: in a nitrogen protective atmosphere, heating to 190-210°C at a rate of 5-10°C / min and keeping warm for 25-35 minutes, then heating to 495-505°C at a heating rate of 10-15°C / min and keeping warm for 1.5-2 hours.
[0017] According to some embodiments of the present application, the aging treatment comprises: immediately subjecting the solution-treated radiation-resistant metal layered composite material to aging treatment under a nitrogen protective atmosphere.
[0018] According to some embodiments of the present application, the temperature of the aging treatment is 180-250° C., and the insulation time is ≥12 h.
[0019] According to another aspect of the present application, there is also provided a radiation-resistant metal layered composite material, which is an Al-3.5Cu-2Mg-Ni alloy-tantalum-tungsten alloy layered composite material;
[0020] The composition and weight percentage of the Al-3.5Cu-2Mg-Ni alloy ingot are as follows: Si: ≤0.5%, Fe: 0.2-0.6%, Cu: 3-3.8%, Mn: ≤0.05%, Mg: 1.8-2.4%, Ni: 0.8-1.2%, Zn: ≤0.3%, Ti: ≤0.5%, the individual content of other elements is ≤0.05%, the total content is ≤0.15%, and the balance is aluminum;
[0021] Among them, the tantalum layer in the Al-3.5Cu-2Mg-Ni alloy-tantalum-tungsten alloy layered composite material accounts for 15%-75%;
[0022] The radiation-resistant metal layered composite material of the present application has a tensile strength of ≥500 MPa, a yield strength of ≥380 MPa, and a shear strength of ≥100 MPa.
[0023] Compared with the prior art, this application has at least the following beneficial effects:
[0024] The present application provides a radiation-resistant metal layered composite material, which is an Al-3.5Cu-2Mg-Ni alloy-tantalum-tungsten alloy layered composite material. A certain amount of Cu, Mg, and Ni are added to the Al-3.5Cu-2Mg-Ni alloy of the present application, which not only improves the alloy's ability to block extranuclear electrons, but also forms precipitation phases such as Al2Cu and Al2CuMg during the aging process, thereby increasing the aging strengthening effect.
[0025] The composite material of the present application has excellent radiation shielding performance. Under the irradiation of the earth-like medium and high orbit continuous electron energy spectrum (0.5 to 5 MeV), under the condition of the same surface density, the shielding protection effect is improved by more than 790% compared with the single aluminum material; and the mechanical properties are better, with a tensile strength of ≥500MPa, a yield strength of ≥380MPa, and a shear strength of ≥100MPa.
[0026] The present application also provides a method for preparing a radiation-resistant metal layered composite material, which does not undergo significant deformation during the heat treatment process, has a good plate shape, and does not require straightening after the heat treatment. At the same time, the preparation method of the present application also includes a homogenization annealing step, which basically eliminates the microsegregation generated during the casting process, is conducive to the uniform distribution of the precipitated phase during subsequent aging, and makes the performance more uniform. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic structural diagram of the radiation-resistant metal layered composite material of the present application.
[0028] Figure 2 Schematic diagram of the proton stopping power of different elements.
[0029] Figure 3 Schematic diagram of the extranuclear electron blocking ability of different elements.
[0030] Figure 4 This is a product picture of the radiation-resistant metal layered composite material prepared in Example 1 of the present application.
[0031] Figure 5 This is a product picture of the radiation-resistant metal layered composite material prepared in Example 2 of the present application.
[0032] Figure 6 This is a product picture of the radiation-resistant metal layered composite material prepared in Example 3 of the present application.
[0033] Figure 7 This is a product picture of the radiation-resistant metal layered composite material prepared in Example 1 of the present application.
[0034] Figure 8 This is a product picture of the radiation-resistant metal layered composite material prepared in comparative examples 2 and 3 of the present application.
[0035] Fig. 9 This is the SEM microstructure morphology of Al-3.5Cu-2Mg-Ni alloy after different homogenization heat treatments.
[0036] Fig.10 This is the SEM microstructure of Al-3.5Cu-2Mg-Ni aluminum alloy after different two-stage homogenization heat treatments. DETAILED DESCRIPTION
[0037] The technical solution of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0038] It is particularly important to point out that similar substitutions and modifications made to the present application are obvious to those skilled in the art, and they are all deemed to be included in the present application. Relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present application to implement and apply the technology of the present application. Obviously, the described embodiments are only some embodiments of the present application, not all embodiments.
[0039] If no specific conditions are specified in this application, the preparation shall be carried out under conventional conditions or the conditions recommended by the manufacturer. The raw materials or excipients used, as well as the reagents or instruments used, for which the manufacturers are not specified, are all conventional products that can be obtained commercially.
[0040] The application is described in detail below.
[0041] Satellites in orbit mainly encounter space radiation environments such as radiation belt electrons, radiation belt protons, solar cosmic ray protons and heavy ions, and galactic cosmic ray protons and heavy ions. Among them, radiation belt electrons and radiation belt protons are the main radiation sources that cause the total dose effect. The shielding effects of materials with different atomic numbers are not the same. In general, materials with high atomic numbers have better shielding effects on electrons, mainly because high atomic number materials have a greater elastic scattering effect on electrons (proportional to Z2 / A). Since materials with low atomic numbers usually have a larger Z / A, the material per unit equivalent thickness has a stronger ability to stop protons. Therefore, shielding of protons generally gives priority to materials with low atomic numbers.
[0042] according to Figure 2 , Figure 3 As shown, Ta and W elements have strong blocking ability for extranuclear electrons, while Al, Mg, Cu, and Ni elements have strong blocking ability for protons. Therefore, the present application adopts Al-3.5Cu-2Mg-Ni alloy and tantalum-tungsten alloy to prepare a new aluminum / tantalum layered composite material by rolling method, and its shielding protection effect is improved by more than 90% compared with single aluminum material under the same surface density.
[0043] The technical solution of the present application is further described below in conjunction with specific embodiments.
[0044] Embodiment 1:
[0045] Composition of Al-3.5Cu-2Mg-Ni alloy ingot: Si element content is 0.4%, Fe element content is 0.52%, Cu element content is 3.7%, Mn element content is 0.01%, Mg element content is 2.4%, Ni element content is 1.1%, Zn element content is 0.01%, and Ti element content is 0.02%.
[0046] Ingot: Al-3.5Cu-2Mg-Ni alloy ingot is melted and cast according to the designed composition ratio; the ingot thickness is 480mm.
[0047] Homogenization treatment: The homogenization process of aluminum alloy ingots is to heat up to 495℃ at a rate of 90℃ / h, keep it warm for 18h, then quickly heat up to 505℃, keep it warm for 12h, and then take it out of the furnace and air cool it after the holding time is completed.
[0048] Hot rolling and annealing: hot rolling heating temperature is 480℃, heating time is 2h, starting rolling temperature is 452℃, final rolling temperature is 300℃, hot rolled plate thickness is 2.6mm, a total of 12 passes are completed, and the reduction of each pass is ≤40%; aluminum alloy hot rolled plate is annealed at 350℃ and holding time is 5h.
[0049] Composite rolling: Use a wire brush to clean the surfaces of the 2.6 mm aluminum alloy plate and the 0.65 mm thick Ta2.5W alloy plate with a louver wheel, stack them and roll them at room temperature, with a reduction of 38.5% per pass to a thickness of 2 mm, of which the thickness of the tantalum layer is 0.4 mm, to obtain a layered composite material.
[0050] The layered composite material was subjected to solution treatment and aging treatment: nitrogen was used as protective gas, heated to 200°C at a rate of 8°C / min and kept at that temperature for 30 minutes, then heated to 500°C at a rate of 12°C / min, kept at 500°C for 1h50min, and immediately transferred to an aging furnace for aging treatment after being taken out. The aging temperature range was 200°C, the holding time was 15h, and then taken out and air-cooled.
[0051] After solution aging treatment, the aluminum-tantalum composite plate has a Figure 4 .
[0052] Embodiment 2:
[0053] Composition of Al-3.5Cu-2Mg-Ni alloy ingot: Si element content is 0.35%, Fe element content is 0.42%, Cu element content is 3.5%, Mn element content is 0.01%, Mg element content is 2.1%, Ni element content is 1.0%, Zn element content is 0.01%, and Ti element content is 0.02%.
[0054] Ingot casting: Al-3.5Cu-2Mg-Ni alloy ingots are melted and cast according to the designed composition ratio; the ingot thickness is 420mm.
[0055] Homogenization treatment: The homogenization process of cast aluminum alloy is to heat up to 493℃ at a rate of 80℃ / h, keep it at that temperature for 16h, then quickly heat up to 510℃, keep it at that temperature for 12h, and then take it out of the furnace and air cool it after the holding time is completed.
[0056] Hot rolling and annealing: hot rolling heating temperature is 470℃, heating time is 2.5h, starting rolling temperature is 445℃, final rolling temperature is 280℃, hot rolled plate thickness is 0.28mm, a total of 14 passes are completed, and the reduction of each pass is ≤40%; aluminum alloy hot rolled plate is annealed at 380℃ and holding time is 4h.
[0057] Composite rolling: The surfaces of 0.28 mm aluminum alloy plate and 0.75 mm thick Ta2.5W alloy plate to be composited were polished clean with a wire brush, stacked and assembled, and then rolled at room temperature with a reduction of 39.8% per pass to a thickness of 0.62 mm, of which the thickness of the tantalum layer was 0.46 mm, to obtain a layered composite material.
[0058] The layered composite material was subjected to solution treatment and aging treatment: nitrogen was used as a protective gas, heated to 200°C at a rate of 6°C / min for 30 minutes, then heated to 495°C at a rate of 10°C / min, and kept at 495°C for 2 hours. After being taken out, it was immediately transferred to an aging furnace for aging treatment. During heating, the tantalum layer was prevented from being oxidized in the furnace. The aging temperature range was 210°C, the holding time was 14 hours, and it was taken out and air-cooled. Nitrogen was used as a protective gas in the furnace during heating to prevent the tantalum layer from being oxidized during the heating process.
[0059] After solution aging treatment, the aluminum-tantalum composite plate has a Figure 5 .
[0060] Embodiment 3:
[0061] Composition of Al-3.5Cu-2Mg-Ni alloy ingot: Si element content is 0.32%, Fe element content is 0.46%, Cu element content is 3.2%, Mn element content is 0.01%, Mg element content is 1.9%, Ni element content is 1.0%, Zn element content is 0.01%, and Ti element content is 0.02%.
[0062] Ingot casting: Al-3.5Cu-2Mg-Ni alloy ingots are melted and cast according to the designed composition ratio; the ingot thickness is 360mm.
[0063] Homogenization treatment: The homogenization process of cast aluminum alloy is to heat up to 498℃ at a rate of 100℃ / h, keep it warm for 13.5h, then quickly heat up to 500℃, keep it warm for 12h, and then take it out of the furnace and air cool it after the holding time is completed.
[0064] Hot rolling annealing: hot rolling heating temperature 470℃, heating time 2h, start rolling temperature 448℃, final rolling temperature 296℃, hot rolled plate thickness 5mm, a total of 10 passes, each pass reduction ≤40%; aluminum alloy hot rolled plate is annealed at 360℃ and holding time 6h.
[0065] Composite rolling: Use a wire brush to clean the surfaces of the 5 mm aluminum alloy plate and the 1.5 mm thick Ta2.5W alloy plate to be composited, stack them and roll them at room temperature, with a reduction of 36.5% per pass to a thickness of 4.13 mm, of which the thickness of the tantalum layer is 0.98 mm, to obtain a layered composite material.
[0066] The layered composite material was subjected to solution treatment and aging treatment: nitrogen was used as a protective gas, heated to 210°C at a rate of 9°C / min for 25 minutes, then heated to 505°C at a rate of 15°C / min, and kept at 505°C for 2 hours. After being taken out, it was immediately transferred to an aging furnace for aging treatment. During heating, the tantalum layer was prevented from being oxidized in the furnace; the aging temperature range was 190°C, the holding time was 18 hours, and it was taken out and air-cooled. During heating, nitrogen was used as a protective gas in the furnace to prevent the tantalum layer from being oxidized during the heating process.
[0067] After solution aging treatment, the shape of the aluminum-tantalum composite plate is shown in 6.
[0068] Comparative Example 1: (Different aluminum alloy compositions, poor mechanical properties, and low radiation resistance)
[0069] Aluminum alloy composition: 1060 aluminum alloy is used, and its chemical composition is as follows: Si element content is 0.15%, Fe element content is 0.18%, Cu element content is 0.03%, Mn element content is 0.02%, Mg element content is 0.02%, Ni element content is 0.01%, Zn element content is 0.01%, Ti element content is 0.01%. Al element content is 99.4%.
[0070] Ingot: Alloy ingots are melted and cast according to the designed composition ratio; the ingot thickness is 480mm.
[0071] Homogenization treatment: The 1060 aluminum alloy ingot is homogenized by heating the ingot to 495°C at a rate of 90°C / h, keeping it for 18 hours, then rapidly heating it to 505°C, keeping it for 12 hours, and then taking it out of the furnace and air cooling it after the holding time is completed.
[0072] Hot rolling and annealing: hot rolling heating temperature is 480℃, heating time is 2h, starting rolling temperature is 455℃, final rolling temperature is 306℃, hot rolled plate thickness is 2.6mm, 12 passes are completed, and the reduction of each pass is ≤40%. 1060 aluminum alloy hot rolled plate is annealed at 350℃ and holding time is 5h.
[0073] Composite rolling: Use a wire brush to clean the surfaces of 2.6 mm 1060 aluminum alloy plate and 0.65 mm thick Ta2.5W alloy plate to be composited, stack them and roll them at room temperature, with a reduction of 38.5% per pass to a thickness of 2 mm, of which the thickness of the tantalum layer is 0.4 mm, to obtain a layered composite material.
[0074] The layered composite material was subjected to solution treatment and aging treatment: nitrogen was used as protective gas, heated to 200°C at a rate of 8°C / min and kept at that temperature for 30 minutes, then heated to 500°C at a rate of 12°C / min, kept at 500°C for 1h50min, and immediately transferred to an aging furnace for aging treatment after being taken out. The aging temperature range was 200°C, the holding time was 15h, and then taken out and air-cooled.
[0075] After solution aging treatment, the aluminum-tantalum composite plate has a Figure 7 .
[0076] Comparative Example 2: (the aluminum alloy composition is the same as that of Example 1, but the solid solution aging process is different, the plate shape is poor, and the performance is slightly lower)
[0077] The layered composite material was subjected to solution treatment and aging treatment: nitrogen was used as protective gas, heated to 500°C at a rate of 12°C / min, kept at this temperature for 1h50min, and then taken out for water cooling. The aging temperature was 200°C, the holding time was 15h, and then taken out for air cooling.
[0078] After solution aging treatment, the aluminum-tantalum composite plate has a Figure 8 (Left).
[0079] Comparative Example 3: (same aluminum alloy composition, different solution aging time, low performance)
[0080] The layered composite material was subjected to solution treatment and aging treatment: nitrogen was used as a protective gas, and the material was heated to 200°C at a rate of 8°C / min and kept at that temperature for 30 minutes, and then heated to 500°C at a rate of 12°C / min, and kept at that temperature for 3 hours. After being taken out, it was immediately transferred to an aging furnace for aging treatment. The aging temperature range was 200°C, the holding time was 10 hours, and it was taken out and air-cooled.
[0081] After solution aging treatment, the aluminum-tantalum composite plate has a Figure 8 (right).
[0082] Comparative Example 4: (the aluminum alloy composition is the same as that of Example 1, but the homogenization process is different)
[0083] Al-3.5Cu-2Mg-Ni alloy ingot composition: Si element content is 0.4%, Fe element content is 0.52%, Cu element content is 3.7%, Mn element content is 0.01%, Mg element content is 2.4%, Ni element content is 1.1%, Zn element content is 0.01%, and Ti element content is 0.02%. (The composition is the same as that of Example 1)
[0084] Ingot casting: Al-3.5Cu-2Mg-Ni alloy ingots were smelted and cast according to the designed composition ratio; the thickness of the ingots was 480 mm. (The specifications of the ingots were the same as those in Example 1)
[0085] Homogenization treatment: The homogenization process of aluminum alloy ingots is to heat up to 490℃ at a rate of 90℃ / h, keep it warm for 18h, then quickly heat up to 498℃, keep it warm for 12h, and then take it out of the furnace and air cool it after the holding time is completed.
[0086] Hot rolling and annealing: hot rolling heating temperature is 480℃, heating time is 2h, starting rolling temperature is 452℃, final rolling temperature is 300℃, hot rolled plate thickness is 2.6mm, a total of 12 passes are completed, and the reduction of each pass is ≤40%; aluminum alloy hot rolled plate is annealed at 350℃ and holding time is 5h.
[0087] Composite rolling: Use a wire brush to clean the surfaces of the 2.6 mm aluminum alloy plate and the 0.65 mm thick Ta2.5W alloy plate with a louver wheel, stack them and roll them at room temperature, with a reduction of 38.5% per pass to a thickness of 2 mm, of which the thickness of the tantalum layer is 0.4 mm, to obtain a layered composite material.
[0088] The layered composite material was subjected to solution treatment and aging treatment: nitrogen was used as protective gas, heated to 200°C at a rate of 8°C / min and kept at that temperature for 30 minutes, then heated to 500°C at a rate of 12°C / min, kept at 500°C for 1h50min, and immediately transferred to an aging furnace for aging treatment after being taken out. The aging temperature range was 200°C, the holding time was 15h, and then taken out and air-cooled.
[0089] Experimental example
[0090] 1. Test the mechanical properties and shielding effectiveness of the composite materials in the above embodiments and comparative examples.
[0091] The shielding protection effect test uses a 90Sr-90Y electron radiation source device to test the shielding protection effect of aluminum / tantalum composite materials of different specifications and the shielding effect of single aluminum materials of equal mass (i.e., equivalent aluminum thickness) under irradiation of a continuous electron energy spectrum (0.5-5 megaelectron volts) in a high earth orbit. Equivalent aluminum thickness = Al layer thickness in the composite material + TaW layer thickness × TaW layer density ÷ Al layer density. For example, in Example 1, the composite material is 1.6 mm aluminum + 0.4 mm tantalum, and the equivalent aluminum thickness is 1.6 + 0.4 × 16.68 ÷ 2.7 = 4 mm.
[0092] The test results are shown in Table 1 and Table 2.
[0093] Table 1
[0094]
[0095]
[0096] Table 2
[0097]
[0098] 2. Test the effect of the homogenization process in the preparation process of this application, such as Fig. 9 , Fig.10 .
[0099] Fig. 9 SEM microstructures of Al-3.5Cu-2Mg-Ni alloy after different homogenization heat treatments, including (a) as-cast; (b) 480℃ / 24h; (c) 490℃ / 24h; (d) 495℃ / 24h (e) 505℃ / 24h. Fig.10 SEM microstructures of Al-3.5Cu-2Mg-Ni aluminum alloy after different two-stage homogenization heat treatments, including (a) 495℃ / 12h+505℃ / 12h; (b) 495℃ / 18h+505℃ / 12h.
[0100] according to Fig. 9 It can be seen that extending the single homogenization treatment time still cannot completely eliminate the unbalanced phase in the ingot; according to Fig.10 It can be seen that a double-stage homogenization treatment with a holding time of ≥1.5h per 40mm thickness can obtain a cleaner and more uniform interface morphology.
[0101] By comparing the microstructural morphology of the aluminum alloy in Example 1 after different homogenization heat treatments, it can be seen that after the alloy is homogenized at 495℃ / 18h+505℃ / 12h, the coarse S(Al2CuMg) phase, AlCuFeMn phase and θ(Al2Cu) phase on the grain boundary are basically completely dissolved back into the matrix, the non-equilibrium crystalline phase on the grain boundary is continuously reduced to be basically completely eliminated, the component segregation is gradually eliminated, and the structure becomes more uniform.
[0102] Through the comparison of the above experimental examples, it can be seen that adding a certain amount of Cu, Mg, and Ni to the Al-3.5Cu-2Mg-Ni alloy of the present application not only improves the radiation shielding ability of the alloy, but also forms precipitation phases such as Al2Cu and Al2CuMg during the aging process, thereby increasing the mechanical properties of the composite material. (Examples 1 to 3 and Comparative Example 1); the heat treatment system of the present application, adding a 200°C heat treatment stage before the solid solution treatment, can effectively prevent the deformation of the composite plate during the solid solution process, and there is no need to straighten it after the heat treatment (Example 1 and Comparative Example 2); heat treatment within the solid solution and aging temperature and time range of the present application can effectively improve the mechanical properties of the composite plate (Example 1 and Comparative Example 3); the homogenization heat treatment system of the present application can eliminate the microsegregation generated during the casting process, which is conducive to the uniform distribution of the precipitation phase during the subsequent aging, making the performance more uniform.
[0103] The description of the above embodiments is only used to help understand the method and core idea of the present application. It should be noted that, for ordinary technicians in this technical field, several improvements and modifications can be made to the present application without departing from the principles of the present application, and these improvements and modifications also fall within the scope of protection of the claims of the present application.
Claims
1. A method for preparing a radiation-resistant metal layered composite material, characterized in that: include: Melting and casting Al-3.5Cu-2Mg-Ni alloy ingot; The Al-3.5Cu-2Mg-Ni alloy ingot is homogenized, hot rolled and annealed; Composite rolling the annealed Al-3.5Cu-2Mg-Ni alloy ingot and a tantalum-tungsten alloy plate to obtain the radiation-resistant metal layered composite material; Among them, the composition and weight percentage of the Al-3.5Cu-2Mg-Ni alloy ingot are: Si: ≤0.5%, Fe: 0.2~0.6%, Cu: 3~3.8%, Mn: ≤0.05%, Mg: 1.8~2.4%, Ni: 0.8~1.2%, Zn: ≤0.3%, Ti: ≤0.5%, the individual content of other elements is ≤0.05%, the total amount is ≤0.15%, and the balance is aluminum.
2. The preparation method according to claim 1, characterized in that: The homogenization treatment includes: heating to 492-498°C at a speed of 80-100°C / h, keeping the temperature for ≥1.5h per 40mm according to the thickness of the alloy ingot, rapidly heating to 500-510°C after the insulation is completed, keeping the temperature for 10-15h, and air cooling after the insulation time is completed.
3. The preparation method according to claim 1, characterized in that: The hot rolling temperature is 470±10°C, the heating time is ≥1.5h, the starting rolling temperature is 440±20°C, the final rolling temperature is ≥270°C, and the reduction in each pass is ≤40%.
4. The preparation method according to claim 1, characterized in that: The annealing temperature is 350-380° C. and the insulation time is 3-6 hours.
5. The preparation method according to claim 1, characterized in that: The reduction amount of a single pass of the composite rolling is 35-40%.
6. The preparation method according to any one of claims 1 to 5, characterized in that: Also includes: The radiation-resistant metal layered composite material is sequentially subjected to a solution treatment and an aging treatment.
7. The preparation method according to claim 6, characterized in that: The solution treatment comprises: heating to 190-210° C. at a rate of 5-10° C. / min and keeping the temperature for 25-35 min under a nitrogen protective atmosphere, then heating to 495-505° C. at a rate of 10-15° C. / min and keeping the temperature for 1.5-2 h.
8. The preparation method according to claim 7, characterized in that: The aging treatment comprises: immediately subjecting the solution-treated radiation-resistant metal layered composite material to aging treatment in a nitrogen protective atmosphere.
9. The preparation method according to claim 8, characterized in that: The temperature of the aging treatment is 180-250° C., and the insulation time is ≥12h.
10. A radiation-resistant metal layered composite material, characterized in that: It is a layered composite material of Al-3.5Cu-2Mg-Ni alloy and tantalum-tungsten alloy; The composition and weight percentage of the Al-3.5Cu-2Mg-Ni alloy ingot are as follows: Si: ≤0.5%, Fe: 0.2-0.6%, Cu: 3-3.8%, Mn: ≤0.05%, Mg: 1.8-2.4%, Ni: 0.8-1.2%, Zn: ≤0.3%, Ti: ≤0.5%, the individual content of other elements is ≤0.05%, the total content is ≤0.15%, and the balance is aluminum; Wherein, the tantalum layer in the Al-3.5Cu-2Mg-Ni alloy-tantalum-tungsten alloy layered composite material accounts for 15%-75%; The tensile strength of the radiation-resistant metal layered composite material is ≥500MPa, the yield strength is ≥380MPa, and the shear strength is ≥100MPa.
Citation Information
Patent Citations
Anti-radiation ODS steel-steel composite plate and preparation method
CN112170531A
Al-Cu-Mg-Fe-Ni series aluminum alloy material and casting process thereof
CN113699420A
Anti-radiation thin-layer composite material for satellite device and preparation method of anti-radiation thin-layer composite material
CN117772790A
Al-Cu-Mg-Fe-Ni aluminum alloy bar and preparation method and application thereof
CN119101839A